EKSPLORASI KONTEKS-KONSEP FISIKA DI PESISIR PANTAI PULAU LEMBEH UNTUK PEMBELAJARAN DI SMP - Meylinda Utami Patras; Patricia Mardiana Silangen; Jeane Vera Tumangkeng (Charm Sains: Jurnal Pendidikan Fisika, 2022)
Exploratory learning about the contexts of physics concepts on the coast of Lembeh Island is an example of the physics learning process by utilizing the natural surroundings as a learning object. The purpose of this study was to determine the contexts of physics concepts found on the coast of Lembeh island and to find out the results of exploration of physics learning on the coast of Lembeh island. The method in this research is exploratory research. This research was conducted through two stages, namely the first stage of research exploration and stage two exploration of research subjects or students. The research subjects were students of SMP Negeri 13 Satap Bitung 2021/2022.